OPTIMALISASI LIMBAH PERTANIAN MELALUI PEMBUATAN PUPUK ORGANIK DALAM UPAYA PENINGKATAN KESEJAHTERAAN MASYARAKAT DI DESA TEMPOS KECAMATAN GERUNG - Tira, Hendri Sakke; Silvia, Hera; Safitri, Arni; Riwu , Anethesa A Hatu; Sofia, Firda Zahwana; Heristia, Geger Maulidan; Almiana, Atika; Luih, Fiktor Tu Bagus; Fadila, M. Riski; Dwiantari, Ni Made Meta; Wibawa, Andhika Satria (Universitas Mataram, 2023)
Tempos Village is a village located in Gerung District, West Lombok Regency. Some of the agricultural areas in Tempos Village are corn, rice, honey, and several fruit plantations. One of the efforts to maximize the growth and productivity of plants is by applying compost. Compost Fertilizer is organic fertilizer derived from plant residues and animal waste that has undergone a process of decomposition or weathering. Socialization and training on the processing of agricultural waste or livestock waste into compost or organic fertilizer were tried. The application of the activity is carried out in a participatory manner, the procedure for this activity puts into practice the concept of integration between the socialization of lecture procedures and the direct application of directly linking residents. The socialization activity can be declared successful in terms of the participants' descriptions of the modules that have been informed and the enthusiasm of all participants can be said to be great. If the socialization participants are able to make processed products that are well exemplified and get a bonus of knowledge about making compost, starting from equipment and materials to the manufacturing process. So that the training on making compost can be declared a success. From the participants showing positive reactions related to product labeling and packaging, they felt optimistic that this could increase the selling value of the product itself and make it more desirable in the market. The compost produced in this practice can be used by residents for sprinkling on agricultural land, plantations, or rice fields. The implementation of the UNRAM Thematic KKN work program with the theme